Digital Transnational Salafi Da'wah and Indonesia’s Hijrah Movement: An International Relations Perspective - Muhammad Gibran Alif Prasetya (UNIDA Gontor, 2026)
The phenomenon of the Hijrah movement among the Indonesian Muslim middle class marks a shift in religious authority towards transnational Salafism which is massively facilitated by digital technology. This study aims to analyze the strategic role of social media in facilitating da'wah transnationalism and measure its determinants of migration decisions in the perspective of International Relations. This study applies a mixed-methods design with a concurrent embedded strategy. Data was collected through an online survey of 100 respondents participating in the Hijrah movement and digital content analysis. Quantitative analysis used Multiple Linear Regression to test the influence of access duration, frequency of interaction, and content preferences, while qualitative data was used to validate ideological narratives. The results of the study showed that social media activities had a significant positive influence on the decision to emigrate with a determination coefficient of 66.5%. Specifically, the frequency of participatory interaction and exposure to transnational ideological narratives were the strongest predictors, outperforming demographic factors. This study concludes that social media functions effectively as an instrument of